Pelatihan Pemasaran Digital Pada Sekolah Menengah Kejuruan Negeri 1 Cikarang - Danny, Muhtajuddin; Naya, Candra; Mulyana, Iwan; Maringan Hutauruk, Basar (VINICHO MEDIA PUBLISINDO, 2024)
The development of digital technology provides great opportunities in the world of marketing, including for Vocational High School (SMK) students who are prepared to enter the world of industry and entrepreneurship. This community service activity aims to improve the understanding and skills of SMKN 1 Cikarang students in digital marketing, so that they are able to utilize technology to market products or services more effectively. The methods used in this activity include training, direct practice, and assistance in creating digital marketing strategies. The materials provided include the use of social media, creative content creation, use of marketplaces, and digital marketing optimization techniques. The results of this activity show an increase in students' understanding and skills in managing digital marketing, which is reflected in their ability to create and implement digital-based marketing strategies. It is hoped that this training can provide long-term benefits for students in facing challenges in the world of work and in developing independent digital-based businesses.